Preparing Psychology Undergraduates for the Future - Laura R. Terry; Laura Chesniak-Phipps (Journal of Scholarly Engagement)
The American Psychological Association (APA) separates student learning outcomes into two categories: foundational and baccalaureate. Foundational outcomes are generally built into the lower level course curriculum of the major and typically include an introductory course as well as a methods course (American Psychological Association, 2013). Baccalaureate indicators include specific expectations that a student who does not plan to continue their education needs in order to perform in the field at the completion of the bachelor’s degree (APA, 2013). In 2014, when a programmatic review was conducted on the undergraduate psychology program, a need for change was identified to ensure the program aligned to guidelines set forth by the APA for undergraduate programs. The guidelines help to confirm that students are prepared for a career in the field or graduate school. For this reason, changes to the curriculum included the addition of a foundational course focusing on research, Introduction to Psychological Research and Ethics. To ensure relevancy, a Cognitive Neuroscience course was added to the program. Finally, baccalaureate courses are to incorporate “expectations for performance at the completion of the major” for students who plan to further their education and for those who do not (APA, 2013, p. 4). For this reason, a Professional Capstone Project course was added to the program. With instructor guidance, the capstone course provides students the opportunity to explore and solidify choices post-graduation. This course has been successful; therefore, it has been used as a model to create capstone courses in other disciplines in the college (Freeman, 2012). However, improvements can still be made to ensure that students are prepared to transition to life post-graduation.